Effects of Quercetin and Genistein on Boar Sperm Characteristics and Porcine IVF Embyo Developments - Tae-Hee Kim; In-Suh Yuh; In-Chul Park; Hee-Tae Cheong; Jong-Taek Kim; Choon-Keun Park; Boo-Keun Yang (The Korean Society of Animal Reproduction and Biotechnology, 2014)
Quercetin and genistein, plentifully present in fruits and vegetables, are flavonoid family members that have antioxidative function and plant-derived phytoestrogen activity. The antioxidative effects of quercetin and genistein on boar sperm characteristics and In Vitro development of IVF embryo were investigated. The sperm motility was increased by addition of genistein 50 μM for 6 hr incubation compared to control (p<0.05). The sperm viability was increased by addition of quercetin 1 and 50 μM and genestein 1 and 50 μM for 3 hr incubation. In addition, the sperm viability seemed to be increased dose-dependantly by addition of quercetin or genistein 1 and 50 μM, respectively (p<0.05). The membrane integrities were not increased by quercetin or genistein treatments for 3 hr or 6 hr incubation period except for quercetin 1 μM for 3 hr incubation. In mitochondrial activities, addition of quercetin 50 μM for 6 hr incubation increased mitochondrial activity but decreased at 100 μM concentration compared with control (p<0.05). When porcine IVF embryos were cultured in PZM-3 medium supplemented with low concentrations of quercetin (1~10 μM), the developmental rates to morula and blastocyst increased but significantly decreased at high concentrations of quercetin (25~50 μM). The highest developmental rate to blastocysts among all concentrations of quercetin was shown at quercetin 10 μM (p<0.05). The developmental rates to morula or blastocysts at low (0.01~1 μM) and high (5~10 μM) concentrations of genistein were not significantly different among all treatment group and genistein did not affect on IVF embryo development. These results suggest that quercetin and genistein seem to have positive effects at certain concentrations on sperm characteristics such as motility, viability and mitochondrial activity. In addition, low concentrations of quercetin (1, 5 and 10 μM) in this experiment, seem to have beneficial effect on porcine IVF embryo development but genistein did not affect on it at all given concentrations (0.01~10 μM).